Antiproliferative properties and structural analysis of newly synthesized Schiff bases bearing pyrazole derivatives and molecular docking studies - Şener, Nesrin; Özkınalı, Sevil; Çelik Altunoğlu, Yasemin; Yerlikaya, Şerife; Gökçe, Halil; Zurnacı, Merve; Gür, Mahmut; Baloğlu, Mehmet Cengiz; Şener, İzzet (Elsevier, 2021)
New pyrazole Schiffbases containing azo groups were synthesized using the condensation reaction between p-nitrobenzaldehyde and (E)-4-(phenyl)-1-H-pyrazole-3,5-diamine in the molar ratio of 1:2. Characterization of the compounds was performed by spectroscopic techniques, including IR, UV-Vis, H-1-NMR and C-13-NMR. Biological activity of the compounds was evaluated by analyzing DNA protection, antimicrobial and anticancer properties. Compound 4 was effective for Salmonella typhimurium with the MIC concentration of 62.5 mu g/mL. Moreover, this compound had the highest protection activity on DNA. Cytotoxic activity of compound 4 was determined on the HeLa cancer cell line with the IC50 concentration of 976.6 mu M. The anti-cancer characteristic of compounds 4 and 5 for HeLa cancer was theoretically analyzed by molecular docking study as well. Among the tested compounds, compound 4 possessed significant results due to its in vitro cytotoxic properties. Therefore, it may be considered as a potential bioactive agent for cancer treatment studies. In addition, further in vivo analysis can be performed to indicate its anticancer property.
Keywords: Antimicrobial Activity; Azo-Imine; Cytotoxic Activity; DNA Protection; Molecular Docking; Pyrazole; Schiff Bases